Challenges of the Provision of Professional Supervision in Facilitating Best Practice in Child Protection Services - Chan, Soak Fong; Azman, Azlinda; Jamir Singh, Paramjit Singh (Asian Social Work Journal, 2025)
Supervision is an important component in social worker practice. The provision of professional supervision is crucial to ensure the delivering of better quality child protection services. The study aims to explore the experience of supervision, specifically the views of respondents on the challenges of the provision of professional supervision in facilitating best practice in child protection services. A cross-sectional design utilizing an exploratory-descriptive qualitative method is identified for this study. The respondents of the study comprise of individuals work within a statutory child protection agency and individuals from non-statutory child protection setting but within other related professional bodies and services systems in relation to child protection. Findings indicate the lacking of a structured and systematic professional supervision, poor supervision in relation to a routinized ‘technical’ operational provision of supervision as well as lack of qualified social work supervisors are some of the most challenging situations in the provision of professional supervision in child proetecion services. The findings also recognize the importance of professional supervision in facilitating and sustaining best practice in child protection services. These findings have great relevance to the organization’s human resource strategic planning and capacity building in the area of social work child protection practice. It can also be a platform and support on the need to develop a more structured professional supervision courses and trainings in the country.